Pangan, kearifan lokal dan keanekaragaman hayati (Cindelaras Pustaka Rakyat Cerdas, 2005)
On agriculture and food supply in Indonesia; collection of articles
Keywords: Aufsatzsammlung; Agriculture and state; Food supply